2008
DOI: 10.1136/bjsm.2007.044875
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of knee joint position sense following anterior cruciate ligament reconstruction

Abstract: We found no evidence of impaired JPS in weight-bearing positions in subjects with ACL reconstruction at a mean follow-up of 11 months after surgery compared with subjects with healthy knees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
(12 reference statements)
6
25
0
12
Order By: Relevance
“…These results are consistent with those reported in the literature and are justified by the fact that both instability and pain are very typical symptoms in this type of ligament injury, as described Peccin et al [15], Bonfim [19] and Mir et al [20]. reported after the anterior cruciate ligament reconstruction there is a loss of knee function due to an altered proprioceptive response of the new ligament.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those reported in the literature and are justified by the fact that both instability and pain are very typical symptoms in this type of ligament injury, as described Peccin et al [15], Bonfim [19] and Mir et al [20]. reported after the anterior cruciate ligament reconstruction there is a loss of knee function due to an altered proprioceptive response of the new ligament.…”
Section: Discussionsupporting
confidence: 91%
“…Persons undergoing arthroscopic knee surgery are primarily concerned about reducing pain and improving function. Traditionally, recovery endpoints in orthopedic surgery research have consisted of clinical ratings, mechanical indices, and functional outcome (i.e., return of good knee function and return to activities) [2][3][4][5][6]7]. However, fewer studies have examined pain outcomes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, other investigators have reported that these sensory modalities do not differ between the surgical and contralateral limbs or compared to healthy controls following ACLR. 10,[14][15][16] Vibratory perception is also reportedly impaired in the ACLR limb compared to the contralateral limb, 11 but does not appear to differ from healthy controls. 11,17 Vibratory perception may serve as a clinically feasible analog to proprioceptive and kinesthetic assessments, as they share common sensory receptors that are transmitted in parallel in the spinal cord.…”
mentioning
confidence: 99%